The Beauty, the Beast and the Cinema. “The Chain Scheme” in Chinese Literature and Cinematography. Part 2 - Elina A. Sarakaeva (Corpus Mundi, 2023)
In the first part of the work, entitled “The Beauty, the Beast and the Red Hare” published in “Corpus Mundi” Vol. 3(2), 2022, I trace the origin of the “Chain Scheme” legend in the Chinese historical chronicles, analyze the development of the plot in the poetry, fiction and other works of art and make conclusions about the interpretation of the main characters’ morals and motivations in pre-modern Chinese culture. In the present paper, which is the second part of the same research, I analyze artistic devices and narrative tropes in TV versions of “Three Kingdoms”, I comment on the changes that the plot has undergone in the course of history and especially in modern TV-dramas and make some conclusions as to the clash of traditional and modern value systems.